2018
DOI: 10.20964/2018.05.21
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 4-Chlorophenol in a Batch Electrochemical Reactor Using BDD Electrodes

Abstract: The influence of current density (j) (0.25, 0.30, 0.25 and 0.40 A/cm 2 ), initial pH (2.6, 6.5 and 12), stirring speed (As) (400, 500 and 600 rpm), and initial concentration of 4-chlorophenol ([4-CP] 0 ) (300, 500 and 700 mg/L) on degradation of persistent pollutant in a batch electrochemical cell without divisions is presented in this paper. The electrochemical cell was composed of two boron-doped diamond electrodes (BDD). The results of the study showed that best conditions for total degradation of 4-CP were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…From these results, it can be concluded that the effect of pH 0 on the 2-CP mineralization extent is negligible. Hence, it is not necessary to modify the pH of the synthetic solution of 2-CP and this is in agreement with previous reports [28].…”
Section: Effect Of Phsupporting
confidence: 92%
See 2 more Smart Citations
“…From these results, it can be concluded that the effect of pH 0 on the 2-CP mineralization extent is negligible. Hence, it is not necessary to modify the pH of the synthetic solution of 2-CP and this is in agreement with previous reports [28].…”
Section: Effect Of Phsupporting
confidence: 92%
“…Among all, oxalic acid is the one with the highest concentration (2.5 mg L −1 ). It is well known that oxalic acid oxidation requires a high • OH concentration The aforementioned results suggest that 2-CP oxidation under the studied reaction conditions here, follows reaction pathway rather similar to that previously proposed for 4-CP oxidation with BDD electrodes also [28]. In such a scheme, Cl atom removal might produce phenol as the first step.…”
Section: By-products Distributionsupporting
confidence: 84%
See 1 more Smart Citation
“…The widely reported carbon-based catalysts include BDD, 21,100,101 graphite, 20,102 activated carbon fiber, 103 carbon nanotubes, 104,105 and granular activated carbon 26,106 . The catalytic performance of representative carbon-based anodes for HOPs degradation is presented in Table 4.…”
Section: Carbon-based Catalystsmentioning
confidence: 99%